Preparation method of recrystallized nano starch with high digestion resistance
Through a combination of biological enzyme treatment, alcohol precipitation treatment and high temperature and high humidity treatment, the starch chain length distribution is regulated, and the problem of easy digestion of nanostarters is solved, and the preparation of high-digestible recrystallized nanostarters is realized. It is suitable for sugar-controlled foods and intestinal sustained release carriers.
Patent Information
- Application Number
- CN202510740935.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-05
- Publication Date
- 2025-07-04
- Estimated Expiration
- 2045-06-05
AI Technical Summary
Existing nanostarches are easily digested quickly after the crystallization structure is damaged, making it difficult to develop starch that is both nanoscale and highly resistant, resulting in limited application in food and drug delivery materials.
Using a combination of biological enzyme treatment, alcohol precipitation treatment and high-temperature and high-humidity treatment, ethanol is introduced through enzymatic starch suspension, super gelatinization temperature, constant temperature stirring and high-humidity and high heat treatment, the long distribution of starch chains is regulated, and the aggregation and migration and rearrangement of starch chains is promoted to form high digestibility recrystallized nanostarch.
It achieves uniform particle size and dense structure of nanostarch, improves the starch's anti-enzyme digestibility, is suitable for sugar-controlled foods and intestinal sustained-release carriers, improves the content of digestible starch, and meets the needs of high-value-added applications.
Smart Images

Figure CN120249419A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to recrystallized nano starch, in particular to a preparation method of highly resistant starch type recrystallized nano starch. Background Art
[0002] Nano starch crystals refer to modified starches obtained by modifying natural starches through physical, chemical or enzymatic means and reducing the size to the nano scale (usually less than 1000 nm). They have a higher specific surface area, dispersibility and modifiability than natural starches and are mainly used in food packaging materials, emulsifiers / stabilizers and drug delivery materials. Nano starch is easily digested quickly due to the destruction of its crystal structure, which conflicts with "resistance". Therefore, developing nano starch that has both nano scale and a high resistant starch content has become a technical difficulty and research focus. Summary of the Invention
[0003] To solve the above problems, the present invention provides a preparation method of highly resistant starch type recrystallized nano starch.
[0004] The present invention provides the following technical solution: A preparation method of highly resistant starch type recrystallized nano starch, comprising the following steps: (1) Biological enzyme treatment: Treating a starch suspension with a biological enzyme to obtain an enzymolysis solution, and inactivating the enzyme in the enzymolysis solution; (2) Alcohol precipitation treatment: Performing alcohol precipitation treatment on the inactivated enzymolysis solution at the super gelatinization temperature, centrifuging to obtain a precipitate for retrogradation and freeze-drying treatment to obtain nano starch crystals; (3) High temperature and high humidity treatment: Recompounding the nano starch crystals with pure water, performing heat preservation treatment in a high temperature environment, centrifuging, and freeze-drying the obtained precipitate to obtain the highly resistant starch type recrystallized nano starch.
[0005] In the present invention, resistant starch refers to the sum of the content of resistant starch and the content of slowly digestible starch.
[0006] Further, the biological enzyme is used for hydrolyzing α-1,6-glycosidic bonds and is one or two of debranching enzyme and pullulanase, with a concentration of 10 - 250 npun per gram of starch, and the treatment time is 1 - 5 h.
[0007] Further, the source of the starch is any one of corn, potato, wheat, cassava, sweet potato, and rice, and the liquid of the starch suspension is a phosphate buffer solution with a pH of 5 - 6.
[0008] Further, the enzyme inactivation is performed at 80 - 100°C.
[0009] Further, the conditions for alcohol precipitation treatment are as follows: Pour absolute ethanol into the enzymatically hydrolyzed solution after enzyme inactivation at the super gelatinization temperature until the volume ratio of ethanol to the enzymatically hydrolyzed solution after enzyme inactivation is 1-3:2. Keep stirring during the process, with the stirring time being 10-90 min, and the super gelatinization temperature range being 70-100 °C.
[0010] Further, the retrogradation conditions are as follows: The retrogradation temperature is 0-5 °C, and the retrogradation time is 24-72 h.
[0011] Further, the mass ratio of nano starch crystals to pure water is 2:3-2:8.
[0012] Further, the conditions for heat preservation treatment in a high-temperature environment are as follows: The temperature setting range is 70-100 °C, and the heat preservation time is 5-30 min.
[0013] Further, the centrifugation conditions are as follows: The relative centrifugal force is 1000-5000×g, and the centrifugation time is 10 min.
[0014] Further, the freeze-drying conditions are as follows: The freezing temperature is below -50 °C, and the drying time is 24-48 h.
[0015] The beneficial effects of the present invention are as follows: (1) The processes of enzymatic directional debranching, water activity regulation, alcohol precipitation-induced nucleation, and high-temperature hydrothermal recrystallization are integrated in series, realizing the whole-process regulation of the uniform dispersion - directional aggregation - structural rearrangement - dense crystallization of starch chains. Through the specific hydrolysis of α-1,6-glycosidic bonds and precise induced aggregation in solution state, the formation of nano starch crystals is effectively promoted, and combined with high hydrothermal conditions, further promotes the migration and serial crystallization of starch chains, significantly enhancing the anti-enzymatic digestion ability of starch; (2) Compared with traditional nano starch preparation methods, the present invention emphasizes the dual optimization of structural reconstruction and crystallization orderliness. It not only obtains nano particles with uniform particle size and dense structure, but also maintains or improves the content of resistant starch, and is particularly suitable for high-value application fields such as sugar-controlled foods, intestinal sustained-release carriers, and functional dietary fibers.
[0016] (3) The process conditions of the present invention are mild, safe, and controllable. Description of the Drawings
[0017] Figure 1 It is the process flow chart of a preparation method of a highly resistant starch recrystallized nano starch of the present invention; Figure 2Scanning electron microscope images (SEM) of the highly resistant starch recrystallized nanoparticles prepared according to the present invention, where (A) is the SEM image of the product prepared in Example 1, (B) is the SEM image of the product prepared in Example 2, (C) is the SEM image of the product prepared in Example 3, (D) is the SEM image of the product prepared in Example 4, and (E) is the SEM image of the product prepared in Example 5; Figure 3 Scanning electron microscope images (SEM) of the starch nanocrystals prepared in Comparative Examples 1 - 3 of the present invention, where (A) is the SEM image of the product prepared in Comparative Example 1, (B) is the SEM image of the product prepared in Comparative Example 2, and (C) is the SEM image of the product prepared in Comparative Example 3; Figure 4 Component content distribution of starch in the examples and comparative examples of the present invention: resistant starch (RS), slowly digestible starch (SDS), and rapidly digestible starch (RDS). Detailed implementation manners
[0018] To further elaborate on the technical means and effects adopted by the present invention to achieve the intended invention purpose, the following will, in conjunction with the attached drawings and preferred embodiments, describe in detail the specific implementation manners, structures, features, and effects according to the present invention.
[0019] The present invention utilizes enzymatic hydrolysis of starch suspension, introduction of ethanol at the super gelatinization temperature, constant temperature stirring, and high - humidity and high - heat treatment to connect processes such as regulating the starch chain length distribution, promoting starch chain aggregation, increasing the degree of freedom and migration ability of starch chains, and accelerating the migration, rearrangement, and crystallization of starch chains, forming a method for preparing highly resistant starch recrystallized nanoparticles. Through the present invention, starch nanocrystals with a resistant starch content > 70% and a relative crystallinity > 50% are prepared, which is expected to become a new method for guiding the production of highly resistant starch recrystallized nanoparticles.
[0020] The following will further illustrate the embodiments of the present invention through multiple examples.
[0021] Example 1 A preparation method of highly resistant to digestion recrystallized nano-starch, using a debranching enzyme with a concentration of 10 npun per gram of starch to treat 100 g of corn starch suspension for 1 h to obtain an enzymolysis solution. The corn starch suspension is prepared from 5 g of corn starch and 95 g of phosphate buffer (pH = 6). After inactivating the enzyme in the enzymolysis solution at 80 °C, anhydrous ethanol is poured into the inactivated enzymolysis solution at 75 °C until the volume ratio of ethanol to the inactivated enzymolysis solution is 1:2. The process is kept stirring, and the stirring time is 10 min. The precipitate is obtained by centrifugation and subjected to retrogradation and freeze-drying treatment. The retrogradation conditions are: the retrogradation temperature is 0 °C, and the retrogradation time is 24 h to obtain nano-starch crystals; the nano-starch crystals are compounded with pure water, and the mass ratio of nano-starch crystals to pure water is 2:3, and they are subjected to heat preservation treatment in a high-temperature environment. The temperature setting range is 70 °C, and the heat preservation time is 30 min; centrifugation is carried out, and the precipitate is freeze-dried. The freeze-drying conditions are: the freezing temperature is -50 °C, and the drying time is 48 h to obtain the highly resistant to digestion recrystallized nano-starch.
[0022] In this example, the relative centrifugal force is 1000×g, and the centrifugation time is 10 min.
[0023] (1) Observation of nano-scale morphology: The starch granules are sieved through a 200-mesh sieve, and a small amount is picked up with a toothpick and evenly smeared on the conductive adhesive, and gold is sprayed in a vacuum environment. A field emission scanning electron microscope is used for observation, and the acceleration voltage is set to 3 kV. In this example, it is observed that the starch morphology presents a nano-scale morphology, a smooth surface, and a compact granular structure in the form of a lump, such as Figure 2 (A) in.
[0024] (2) Particle size measurement: Weigh 20 mg of starch granules into a 50 ml centrifuge tube respectively, add 20 ml of deionized water to prepare a 1 mg / ml (w / v) suspension, and homogenize at high speed at 15000 rpm for 2 min to uniformly disperse the starch granules in the aqueous phase. Absorb 1 ml of the liquid and inject it into the sample cell, and measure the particle size distribution at 25 °C with a nanoparticle and Zeta potential analyzer. In this example, the particle size of the recrystallized nano-starch is 859 nm.
[0025] (3)Determination of resistant starch content: Mix 790 ml of 0.2 mol / L sodium acetate solution with 210 ml of 0.2 mol / l acetic acid solution, add 0.04 mol of calcium chloride, and stir until completely mixed and dissolved to obtain a buffer solution; Weigh 2 g of pancreatin and add it to 20 ml of the above buffer solution. After stirring for 20 min, centrifuge at 4000 rpm for 10 min, take the supernatant, and mix the supernatant with glucoamylase in a volume ratio of 170:7 to obtain a mixed enzyme solution. Weigh 40 mg of starch granules passed through a 60-mesh sieve into each labeled centrifuge tube, add 4 ml of acetate buffer solution, 0.8 ml of the mixed enzyme solution and 3 glass beads, and place them in a constant temperature water bath and shake at 270 rpm at 37°C. Samples are taken at 0 min, 20 min, and 120 min respectively, added with 24 ml of absolute ethanol to inactivate the enzyme, centrifuged at 4000 rpm for 10 min to obtain the supernatant digestive juice, and the glucose content in the supernatant digestive juice is measured using a glucose oxidase detection kit. Mark the glucose contents measured in the supernatant digestive juice at 0, 20, and 120 min as G0, G20, and G120 respectively. The calculation formulas for the contents of RDS, SDS, and RS are as follows: RDS (%) = (G20 − G0) × 0.9 × 100 / 0.04; SDS (%) = (G120 – G20) × 0.9 × 100 / 0.04; RS (%) = 1 − RDS (%) − SDS (%); Among them, 0.04 represents the total amount of starch is 0.04 g, and 0.9 represents the glucose group conversion coefficient.
[0026] In this example, the measured value of G120 is 0.644, the value of G20 is 0.63, the value of G0 is 0.62. The content of resistant starch (RS) in the recrystallized nanometer starch is 44%, the content of slowly digestible starch (SDS) is 31%, and the total content of resistant starch is 75%.
[0027] Example 2 A preparation method of highly resistant to digestion recrystallized nano-starch, using pullulanase with a concentration of 60 npun per gram of starch to treat 100 g of potato starch suspension for 2 h to obtain an enzymolysis solution. The potato starch suspension is prepared from 5 g of potato starch and 95 g of phosphate buffer (pH = 5). After inactivating the enzyme in the enzymolysis solution at 85 °C, absolute ethanol is poured into the inactivated enzymolysis solution at 80 °C until the volume ratio of ethanol to the inactivated enzymolysis solution is 1.5:2. Stirring is maintained during the process, and the stirring time is 30 min. The precipitate is obtained by centrifugation and subjected to retrogradation and freeze-drying treatment. Retrogradation conditions: the retrogradation temperature is 1 °C, and the retrogradation time is 36 h to obtain nano-starch crystals; the nano-starch crystals are compounded with pure water, and the mass ratio of nano-starch crystals to pure water is 2:4, and they are subjected to heat preservation treatment in a high-temperature environment. The temperature setting range is 76 °C, and the heat preservation time is 12 min; centrifugation is carried out, and the precipitate is freeze-dried. Freeze-drying conditions: the freezing temperature is -55 °C, and the drying time is 42 h to obtain the highly resistant to digestion recrystallized nano-starch.
[0028] In this example, the relative centrifugal force is 2000×g, and the centrifugation time is 10 min.
[0029] (1) Observation of nano-scale morphology: The starch granules are sieved through a 200-mesh sieve, and a small amount is picked up with a toothpick and evenly smeared on the conductive glue, and gold is sprayed in a vacuum environment. A field emission scanning electron microscope is used for observation, and the acceleration voltage is set to 3 kV. In this example, it is observed that the starch granules exhibit nano-scale morphology, a dense prismatic structure and a nano-scale network structure, as shown in Figure 2 (B) in.
[0030] (2) Particle size determination: Weigh 20 mg of starch granules into a 50 ml centrifuge tube respectively, add 20 ml of deionized water to prepare a 1 mg / ml (w / v) suspension, and homogenize at high speed at 15000 rpm for 2 min to uniformly disperse the starch granules in the aqueous phase. Absorb 1 ml of the liquid and inject it into the sample cell, and use a nanoparticle and Zeta potential analyzer to measure the particle size distribution at 25 °C. In this example, the particle size of the recrystallized nano-starch crystals is 624 nm.
[0031] (3)Determination of resistant starch content: Mix 790 ml of 0.2 mol / l sodium acetate solution with 210 ml of 0.2 mol / l acetic acid solution, add 0.04 mol of calcium chloride, and stir until completely mixed and dissolved to obtain a buffer solution; weigh 2 g of pancreatin and add it to 20 ml of the above buffer solution. After stirring for 20 min, centrifuge at 4000 rpm for 10 min, take the supernatant, and mix the supernatant with glucoamylase in a volume ratio of 170:7 to obtain a mixed enzyme solution. Weigh 40 mg of starch granules passed through a 60-mesh sieve into each of the labeled centrifuge tubes, add 4 ml of acetate buffer solution, 0.8 ml of the mixed enzyme solution, and 3 glass beads, and place them in a constant temperature water bath and shake at 270 rpm at 37 °C. Samples are taken at 0 min, 20 min, and 120 min respectively, added with 24 ml of absolute ethanol to inactivate the enzyme, centrifuged at 4000 rpm for 10 min, and the supernatant digestive juice is used to measure the glucose content in the supernatant digestive juice with a glucose oxidase detection kit. Mark the glucose contents measured in the supernatant digestive juice at 0, 20, and 120 min as G0, G20, and G120 respectively. The calculation formulas for the contents of RDS, SDS, and RS are as follows: RDS (%) = (G20 − G0) × 0.9 × 100 / 0.04; SDS (%) = (G120 – G20) × 0.9 × 100 / 0.04; RS (%) = 1 − RDS (%) − SDS (%); Among them, 0.04 represents that the total amount of starch is 0.04 g, and 0.9 represents the glucose group conversion coefficient.
[0032] In this example, the measured value of G120 is 0.89, the value of G20 is 0.889, and the value of G0 is 0.879. Therefore, the content of resistant starch (RS) in the recrystallized nano-starch is 61%, the content of slowly digestible starch (SDS) is 15%, and the total content of resistant starch is 76%.
[0033] Example 3 A preparation method of highly resistant to digestion recrystallized nano-starch. Use a debranching enzyme with a concentration of 110 npun per gram of starch to treat 100 g of wheat starch suspension for 3 h to obtain an enzymolysis solution. The wheat starch suspension is prepared from 5 g of wheat starch and 95 g of phosphate buffer (pH = 6). After inactivating the enzyme in the enzymolysis solution at 90 °C, pour absolute ethanol into the inactivated enzymolysis solution at 90 °C until the volume ratio of ethanol to the inactivated enzymolysis solution is 2:2. Keep stirring during the process, and the stirring time is 50 min. Centrifuge to obtain a precipitate for retrogradation and freeze-drying treatment. Retrogradation conditions: the retrogradation temperature is 2 °C, and the retrogradation time is 48 h to obtain nano-starch crystals; compound the nano-starch crystals with pure water, and the mass ratio of nano-starch crystals to pure water is 2:5. Perform heat preservation treatment in a high-temperature environment, the temperature setting range is 82 °C, and the heat preservation time is 19 min; centrifuge, obtain the precipitate and freeze-dry it. Freeze-drying conditions: the freezing temperature is -60 °C, and the drying time is 36 h to obtain the highly resistant to digestion recrystallized nano-starch.
[0034] In this example, the relative centrifugal force is 3000×g, and the centrifugation time is 10 min.
[0035] (1)Observation of nano-scale morphology: Pass the starch granules through a 200-mesh sieve, dip a small amount with a toothpick and evenly smear it on the conductive adhesive, and spray gold in a vacuum environment. Use a field emission scanning electron microscope for observation, and set the acceleration voltage to 3 kV. In this example, it is observed that the starch granules present a nano-scale morphology, also presenting a dense prismatic structure and a nano-scale network structure, as shown in Figure 2 (C)in.
[0036] (2)Particle size determination: Weigh 20 mg of starch granules into a 50 ml centrifuge tube respectively, add 20 ml of deionized water to prepare a 1 mg / ml (w / v) suspension, and homogenize at a high speed of 15000 rpm for 2 min to uniformly disperse the starch granules in the aqueous phase. Pipette 1 ml of the liquid into the sample cell, and use a nanoparticle and Zeta potential analyzer to measure the particle size distribution at 25 °C. In this example, the particle size of the recrystallized nano-starch is 748 nm.
[0037] (3)Determination of resistant starch content: Mix 790 ml of 0.2 mol / l sodium acetate solution with 210 ml of 0.2 mol / l acetic acid solution, add 0.04 mol of calcium chloride, and stir until completely mixed and dissolved to obtain a buffer solution; weigh 2 g of pancreatin and add it to 20 ml of the above buffer solution. After stirring for 20 min, centrifuge at 4000 rpm for 10 min, take the supernatant, and mix the supernatant with glucoamylase at a volume ratio of 170:7 to prepare a mixed enzyme solution. Weigh 40 mg of starch granules passing through a 60-mesh sieve into each labeled centrifuge tube, add 4 ml of acetate buffer solution, 0.8 ml of the mixed enzyme solution, and 3 glass beads, and place them in a constant temperature water bath and shake at 270 rpm at 37 °C. Take samples at 0 min, 20 min, and 120 min respectively, add 24 ml of absolute ethanol to inactivate the enzyme, centrifuge at 4000 rpm for 10 min, and then use a glucose oxidase detection kit to measure the glucose content in the supernatant digestion solution. Mark the glucose contents measured in the supernatant digestion solutions at 0, 20, and 120 min as G0, G20, and G120 respectively. The calculation formulas for the contents of RDS, SDS, and RS are as follows: RDS (%) = (G20 − G0) × 0.9 × 100 / 0.04; SDS (%) = (G120 – G20) × 0.9 × 100 / 0.04; RS (%) = 1 − RDS (%) − SDS (%); Among them, 0.04 represents that the total amount of starch is 0.04 g, and 0.9 represents the glucose group conversion coefficient.
[0038] In this example, the value of G120 was measured as 0.936, the value of G20 was 0.933, and the value of G0 was 0.925. Therefore, the content of resistant starch (RS) in the recrystallized nano-starch was 74%, the content of slowly digestible starch (SDS) was 6%, and the total content of resistant starch was 80%.
[0039] Example 4 A preparation method of highly resistant-to-digestibility recrystallized nano starch. Treat a 100 g cassava starch suspension with pullulanase at a concentration of 160 npun per gram of starch for 4 h to obtain an enzymolysis solution. The cassava starch suspension is prepared from 5 g of cassava starch and 95 g of phosphate buffer (pH = 5). After inactivating the enzyme in the enzymolysis solution at 95 °C, pour absolute ethanol into the inactivated enzymolysis solution at 90 °C until the volume ratio of ethanol to the inactivated enzymolysis solution is 2.5:2. Keep stirring during the process, and the stirring time is 70 min. Centrifuge to obtain a precipitate for retrogradation and freeze-drying treatment. Retrogradation conditions: the retrogradation temperature is 3 °C, and the retrogradation time is 60 h to obtain nano starch crystals; Recompound the nano starch crystals with pure water, and the mass ratio of nano starch crystals to pure water is 2:6. Carry out heat preservation treatment in a high-temperature environment, the temperature setting range is 90 °C, and the heat preservation time is 25 min; Centrifuge, take the precipitate for freeze-drying, freeze-drying conditions: the freezing temperature is -65 °C, and the drying time is 30 h to obtain the highly resistant-to-digestibility recrystallized nano starch.
[0040] In this example, the relative centrifugal force is 4000×g, and the centrifugation time is 10 min.
[0041] (1) Observation of nano-scale morphology: Pass the starch granules through a 200-mesh sieve, dip a small amount with a toothpick and evenly smear it on the conductive glue, and spray gold in a vacuum environment. Use a field emission scanning electron microscope for observation, and set the acceleration voltage to 3 kV. In this example, it is observed that the starch granules present a nano-scale morphology, showing a dense prismatic structure and a nano-scale network structure, as Figure 2 shown in (D).
[0042] (2) Particle size determination: Weigh 20 mg of starch granules into a 50 ml centrifuge tube respectively, add 20 ml of deionized water to prepare a 1 mg / ml (w / v) suspension, and homogenize at high speed at 15000 rpm for 2 min to uniformly disperse the starch granules in the aqueous phase. Pipette 1 ml of the liquid into the sample cell, and measure the particle size distribution at 25 °C with a nanoparticle and Zeta potential analyzer. In this example, the particle size of the recrystallized nano starch is 636 nm.
[0043] (3)Determination of resistant starch content: Mix 790 ml of 0.2 mol / l sodium acetate solution with 210 ml of 0.2 mol / l acetic acid solution, add 0.04 mol of calcium chloride, and stir until completely mixed and dissolved to obtain a buffer solution; weigh 2 g of pancreatin and add it to 20 ml of the above buffer solution. After stirring for 20 min, centrifuge at 4000 rpm for 10 min, take the supernatant, and mix the supernatant with glucoamylase at a volume ratio of 170:7 to obtain a mixed enzyme solution. Weigh 40 mg of starch granules passing through a 60-mesh sieve into each labeled centrifuge tube, add 4 ml of acetate buffer solution, 0.8 ml of the mixed enzyme solution, and 3 glass beads, and place them in a constant temperature water bath and shake at 270 rpm at 37 °C. Samples are taken at 0 min, 20 min, and 120 min respectively, and the enzyme is inactivated by adding 24 ml of absolute ethanol. After centrifuging at 4000 rpm for 10 min, the supernatant digestion solution is measured for the glucose content in the supernatant digestion solution using a glucose oxidase detection kit. Mark the glucose contents measured in the supernatant digestion solutions at 0, 20, and 120 min as G0, G20, and G120 respectively. The content calculation formulas for RDS, SDS, and RS are as follows: RDS (%) = (G20 − G0) × 0.9 × 100 / 0.04; SDS (%) = (G120 – G20) × 0.9 × 100 / 0.04; RS (%) = 1 − RDS (%) − SDS (%); Among them, 0.04 represents the total amount of starch is 0.04 g, and 0.9 represents the glucose group conversion coefficient.
[0044] In this example, the value of G120 was measured to be 0.787, the value of G20 was 0.785, and the value of G0 was 0.777. Therefore, the content of resistant starch (RS) in the recrystallized nano-starch was 76%, the content of slowly digestible starch (SDS) was 5%, and the total content of resistant starch was 81%.
[0045] Example 5 A preparation method of highly resistant-to-digestive recrystallized nano starch. Use debranching enzyme and pullulanase with a mass ratio of 1:1 and a concentration of 250 npun per gram of starch to treat 100 g of sweet potato starch suspension for 5 h to obtain an enzymatic hydrolysate. The sweet potato starch suspension is prepared from 5 g of sweet potato starch and 95 g of phosphate buffer solution (pH = 5.5). After inactivating the enzyme in the enzymatic hydrolysate at 100 °C, pour absolute ethanol into the inactivated enzymatic hydrolysate at 95 °C until the volume ratio of ethanol to the inactivated enzymatic hydrolysate is 3:2. Keep stirring during the process, and the stirring time is 90 min. Centrifuge to obtain a precipitate for retrogradation and freeze-drying treatment. Retrogradation conditions: the retrogradation temperature is 5 °C, and the retrogradation time is 24 h to obtain nano starch crystals; Recompound the nano starch crystals with pure water, and the mass ratio of nano starch crystals to pure water is 2:8. Perform heat preservation treatment in a high-temperature environment, the temperature setting range is 100 °C, and the heat preservation time is 30 min; Centrifuge, and freeze-dry the obtained precipitate. Freeze-drying conditions: the freezing temperature is -70 °C, and the drying time is 24 h to obtain the highly resistant-to-digestive recrystallized nano starch.
[0046] In this example, the relative centrifugal force is 5000×g, and the centrifugation time is 10 min.
[0047] (1) Observation of nano-scale morphology: Pass the starch granules through a 200-mesh sieve, dip a small amount with a toothpick and evenly smear it on the conductive glue, and spray gold in a vacuum environment. Use a field emission scanning electron microscope for observation, and set the acceleration voltage to 3 kV. In this example, it is observed that the starch granules present a nano-scale morphology, also presenting a dense prismatic structure and a nano-scale network structure, as Figure 2 (E) in.
[0048] (2) Particle size measurement: Weigh 20 mg of starch granules into a 50 ml centrifuge tube respectively, add 20 ml of deionized water to prepare a 1 mg / ml (w / v) suspension, and homogenize at high speed at 15000 rpm for 2 min to uniformly disperse the starch granules in the aqueous phase. Pipette 1 ml of the liquid into the sample cell, and use a nanoparticle and Zeta potential analyzer to measure the particle size distribution at 25 °C. In this example, the particle size of the nano starch crystals is 758 nm.
[0049] (3)Determination of resistant starch content: Mix 790 ml of 0.2 mol / l sodium acetate solution with 210 ml of 0.2 mol / l acetic acid solution, add 0.04 mol of calcium chloride, and stir until completely mixed and dissolved to obtain a buffer solution; weigh 2 g of pancreatin and add it to 20 ml of the above buffer solution. After stirring for 20 min, centrifuge at 4000 rpm for 10 min, take the supernatant, and mix the supernatant with glucoamylase in a volume ratio of 170:7 to obtain a mixed enzyme solution. Weigh 40 mg of starch granules passed through a 60-mesh sieve into each labeled centrifuge tube, add 4 ml of acetate buffer solution, 0.8 ml of the mixed enzyme solution, and 3 glass beads, and place them in a constant temperature water bath and shake at 37 °C at 270 rpm. Samples are taken at 0 min, 20 min, and 120 min respectively, added with 24 ml of absolute ethanol to inactivate the enzyme, centrifuged at 4000 rpm for 10 min, and the supernatant digestive juice is measured for the glucose content in the supernatant digestive juice using a glucose oxidase detection kit. Mark the glucose contents measured in the supernatant digestive juice at 0, 20, and 120 min as G0, G20, and G120 respectively. The calculation formulas for the contents of RDS, SDS, and RS are as follows: RDS (%) = (G20 − G0) × 0.9 × 100 / 0.04; SDS (%) = (G120 – G20) × 0.9 × 100 / 0.04; RS (%) = 1 − RDS (%) − SDS (%); Among them, 0.04 represents the total amount of starch is 0.04 g, and 0.9 represents the glucose group conversion coefficient.
[0050] In this example, the value of G120 is 0.68, the value of G20 is 0.678, and the value of G0 is 0.67. Therefore, the content of resistant starch (RS) in the recrystallized nano-starch is 77%, the content of slowly digestible starch (SDS) is 5%, and the total content of resistant starch is 82%.
[0051] Comparative Example 1 The difference between this comparative example and Example 1 is that there is no high-temperature and high-humidity treatment step.
[0052] The debranched enzyme with a concentration of 10 npun per gram of starch was used to treat 100 g of corn starch suspension for 1 h to obtain an enzymolysis solution. The corn starch suspension was prepared from 5 g of corn starch and 95 g of phosphate buffer (pH = 6). After inactivating the enzyme in the enzymolysis solution at 90 °C, absolute ethanol was poured into the inactivated enzymolysis solution at 75 °C until the volume ratio of ethanol to the inactivated enzymolysis solution was 1:2. Stirring was maintained during the process for 10 min. The precipitate was obtained by centrifugation and subjected to retrogradation and freeze-drying treatments. The retrogradation conditions were: retrogradation temperature of 0 °C and retrogradation time of 24 h to obtain nano starch crystals.
[0053] In this example, the relative centrifugal force was 1000×g and the centrifugation time was 10 min.
[0054] (1) Observation of nano-scale morphology: The starch granules were sieved through a 200-mesh sieve. A small amount was picked up with a toothpick and evenly smeared on the conductive adhesive, and gold was sprayed in a vacuum environment. Observation was carried out using a field emission scanning electron microscope, and the acceleration voltage was set at 3 kV. In this example, it was observed that the starch granules presented a relatively loose nano starch granule structure, such as Figure 3 (A) in.
[0055] (2) Particle size determination: 20 mg of starch granules were weighed into a 50 ml centrifuge tube respectively, and 20 ml of deionized water was added to prepare a 1 mg / ml (w / v) suspension. High-speed homogenization was carried out at 15000 rpm for 2 min to uniformly disperse the starch granules in the aqueous phase. 1 ml of the liquid was aspirated and injected into the sample cell, and the particle size distribution was measured at 25 °C using a nanoparticle and Zeta potential analyzer. In this example, the particle size of the nano starch crystals was 914 nm.
[0056] (3)Determination of resistant starch content: Mix 790 ml of 0.2 mol / l sodium acetate solution with 210 ml of 0.2 mol / l acetic acid solution, add 0.04 mol of calcium chloride, and stir until completely mixed and dissolved to obtain a buffer solution; weigh 2 g of pancreatin and add it to 20 ml of the above buffer solution. After stirring for 20 min, centrifuge at 4000 rpm for 10 min, take the supernatant, and mix the supernatant with glucoamylase in a volume ratio of 170:7 to prepare a mixed enzyme solution. Weigh 40 mg of starch granules passed through a 60-mesh sieve into each labeled centrifuge tube, add 4 ml of acetate buffer solution, 0.8 ml of the mixed enzyme solution and 3 glass beads, and place it in a constant temperature water bath and shake at 270 rpm at 37 °C. Samples are taken at 0 min, 20 min, and 120 min respectively, added with 24 ml of absolute ethanol to inactivate the enzyme, centrifuged at 4000 rpm for 10 min, and the supernatant digestive juice is used to measure the glucose content in the supernatant digestive juice with a glucose oxidase detection kit. Mark the glucose contents measured in the supernatant digestive juice at 0, 20, and 120 min as G0, G20, and G120 respectively. The calculation formulas for the contents of RDS, SDS, and RS are as follows: RDS (%) = (G20 − G0) × 0.9 × 100 / 0.04; SDS (%) = (G120 – G20) × 0.9 × 100 / 0.04; RS (%) = 1 − RDS (%) − SDS (%); Among them, 0.04 represents the total amount of starch is 0.04 g, and 0.9 represents the glucose group conversion coefficient.
[0057] In this comparative example, the value of G120 was measured as 0.7864, the value of G20 was 0.786, and the value of G0 was 0.758. Therefore, the content of resistant starch (RS) in the nano starch crystal was 36%, the content of slowly digestible starch (SDS) was 1%, and the total content of resistant starch was 37%. It shows that high temperature and high humidity are important technological means to increase the content of resistant starch.
[0058] Comparative Example 2 The difference between this comparative example and Example 1 is that there is no biological enzyme treatment and enzyme inactivation treatment.
[0059] Take 100 g of corn starch suspension, which is prepared from 5 g of corn starch and 95 g of phosphate buffer solution (pH = 6). Pour absolute ethanol into the corn starch suspension at 75 °C until the volume ratio of ethanol to corn starch suspension is 1:2. Keep stirring during the process, and the stirring time is 10 min. Centrifuge to obtain the precipitate for retrogradation and freeze-drying treatment. Retrogradation conditions: the retrogradation temperature is 0 °C, and the retrogradation time is 24 h to obtain nano starch crystals; Recompound the nano starch crystals with pure water, and the mass ratio of nano starch crystals to pure water is 2:3. Keep it in a high-temperature environment for heat preservation treatment, the temperature range is set at 70 °C, and the heat preservation time is 30 min; Centrifuge and freeze-dry the obtained precipitate. Freeze-drying conditions: the freezing temperature is -50 °C, and the drying time is 48 h to obtain the recrystallized starch.
[0060] In this example, the relative centrifugal force is 1000×g, and the centrifugation time is 10 min.
[0061] (1) Observation of nano-scale morphology: Sieve the starch granules through a 200-mesh sieve, dip a small amount with a toothpick and evenly smear it on the conductive adhesive, and spray gold in a vacuum environment. Observe using a field emission scanning electron microscope, and set the acceleration voltage to 3 kV. In this example, it is observed that the starch morphology presents loose starch granules with a size of more than 1 μm, as shown in Figure 3 (B) in.
[0062] (2) Particle size measurement: Weigh 20 mg of starch granules into a 50 ml centrifuge tube respectively, add 20 ml of deionized water to prepare a 1 mg / ml (w / v) suspension, and homogenize at a high speed of 15000 rpm for 2 min to uniformly disperse the starch granules in the aqueous phase. Pipette 1 ml of the liquid into the sample cell, and measure the particle size distribution at 25 °C using a nanoparticle and Zeta potential analyzer. In this example, the particle size of the recrystallized starch is 1127 nm.
[0063] (3) Determination of resistant starch content: Mix 790 ml of 0.2 mol / l sodium acetate solution with 210 ml of 0.2 mol / l acetic acid solution, add 0.04 mol of calcium chloride, and stir until completely mixed and dissolved to obtain a buffer solution; weigh 2 g of pancreatin and add it to 20 ml of the above buffer solution. After stirring for 20 min, centrifuge at 4000 rpm for 10 min, take the supernatant, and mix the supernatant with glucoamylase at a volume ratio of 170:7 to obtain a mixed enzyme solution. Weigh 40 mg of starch granules passed through a 60-mesh sieve into each labeled centrifuge tube, add 4 ml of acetate buffer solution, 0.8 ml of the mixed enzyme solution, and 3 glass beads, and place them in a constant temperature water bath and shake at 37 °C at 270 rpm. Samples are taken at 0 min, 20 min, and 120 min respectively, added with 24 ml of absolute ethanol to inactivate the enzyme, centrifuged at 4000 rpm for 10 min, and the supernatant digestion solution is used to measure the glucose content in the supernatant digestion solution with a glucose oxidase detection kit. Mark the glucose contents measured in the supernatant digestion solutions at 0, 20, and 120 min as G0, G20, and G120 respectively. The calculation formulas for the contents of RDS, SDS, and RS are as follows: RDS (%) = (G20 − G0) × 0.9 × 100 / 0.04; SDS (%) = (G120 – G20) × 0.9 × 100 / 0.04; RS (%) = 1 − RDS (%) − SDS (%); Among them, 0.04 represents that the total amount of starch is 0.04 g, and 0.9 represents the glucose group conversion coefficient.
[0064] In this comparative example, the value of G120 was measured to be 0.902, the value of G20 was 0.896, and the value of G0 was 0.866. Therefore, the content of resistant starch (RS) in the recrystallized starch was 20%, the content of slowly digestible starch (SDS) was 13%, and the total content of resistant starch was 33%. It shows that hydrolysis at a certain enzyme concentration is a necessary process to reach the nanoscale.
[0065] Comparative Example 3 The difference between this comparative example and Example 1 is that there is no alcohol precipitation treatment.
[0066] The debranching enzyme with a concentration of 10 npun per gram of starch was used to treat 100 g of corn starch suspension for 1 h to obtain an enzymolysis solution. The corn starch suspension was prepared from 5 g of corn starch and 95 g of phosphate buffer (pH = 6). After inactivating the enzyme in the enzymolysis solution at 90 °C, centrifugation was carried out to obtain a precipitate for retrogradation and freeze-drying treatment. The retrogradation conditions were as follows: the retrogradation temperature was 0 °C and the retrogradation time was 24 h to obtain nano starch crystals; the nano starch crystals were compounded with pure water, and the mass ratio of the nano starch crystals to pure water was 2:3, and they were heat-treated in a high-temperature environment. The temperature was set in the range of 70 °C and the heat-treatment time was 30 min; centrifugation was carried out, and the obtained precipitate was freeze-dried. The freeze-drying conditions were as follows: the freezing temperature was -50 °C and the drying time was 48 h to obtain the recrystallized starch.
[0067] In this example, the relative centrifugal force was 1000×g and the centrifugation time was 10 min.
[0068] (1) Observation of nano-scale morphology: The starch granules were sieved through a 200-mesh sieve, and a small amount was picked up with a toothpick and evenly smeared on the conductive adhesive, and gold was sprayed in a vacuum environment. A field emission scanning electron microscope was used for observation, and the acceleration voltage was set at 3 kV. In this example, it was observed that the starch morphology presented dense starch granules with a size of more than 1 um, and there was no network structure, such as Figure 3 in (C).
[0069] (2) Particle size determination: 20 mg of starch granules were weighed into a 50 ml centrifuge tube respectively, and 20 ml of deionized water was added to prepare a 1 mg / ml (w / v) suspension. High-speed homogenization was carried out at 15000 rpm for 2 min to uniformly disperse the starch granules in the aqueous phase. 1 ml of the liquid was aspirated and injected into the sample cell, and the particle size distribution was measured with a nanoparticle and Zeta potential analyzer at 25 °C. In this example, the particle size of the nano starch crystals was 1374 nm.
[0070] (3)Determination of resistant starch content: Mix 790 ml of 0.2 mol / l sodium acetate solution with 210 ml of 0.2 mol / l acetic acid solution, add 0.04 mol of calcium chloride, and stir until completely mixed and dissolved to obtain a buffer solution; weigh 2 g of pancreatin and add it to 20 ml of the above buffer solution. After stirring for 20 min, centrifuge at 4000 rpm for 10 min, take the supernatant, and mix the supernatant with glucoamylase in a volume ratio of 170:7 to obtain a mixed enzyme solution. Weigh 40 mg of starch granules passed through a 60-mesh sieve into each labeled centrifuge tube, add 4 ml of acetate buffer solution, 0.8 ml of the mixed enzyme solution, and 3 glass beads, and place them in a constant temperature water bath and shake at 270 rpm at 37 °C. Samples are taken at 0 min, 20 min, and 120 min respectively, added with 24 ml of absolute ethanol to inactivate the enzyme, centrifuged at 4000 rpm for 10 min, and the supernatant digestion solution is used to measure the glucose content in the supernatant digestion solution with a glucose oxidase detection kit. Mark the glucose contents measured in the supernatant digestion solutions at 0, 20, and 120 min as G0, G20, and G120 respectively. The calculation formulas for the contents of RDS, SDS, and RS are as follows: RDS (%) = (G20 − G0) × 0.9 × 100 / 0.04; SDS (%) = (G120 – G20) × 0.9 × 100 / 0.04; RS (%) = 1 − RDS (%) − SDS (%); Among them, 0.04 represents the total amount of starch is 0.04 g, and 0.9 represents the glucose group conversion coefficient.
[0071] In this comparative example, the value of G120 was measured to be 0.993, the value of G20 was 0.986, and the value of G0 was 0.954. Therefore, the content of resistant starch (RS) in the recrystallized starch is 14%, the content of slowly digestible starch (SDS) is 15%, and the total content of resistant starch is 29%. It shows that alcohol precipitation is an important process for forming a nano-scale network structure.
[0072] The above are only the preferred embodiments of the present invention, and do not impose any formal limitations on the present invention. Although the present invention has been disclosed above with the preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications to the equivalent embodiments by using the disclosed technical content within the scope of the technical solution of the present invention. However, as long as it does not depart from the content of the technical solution of the present invention, any brief modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A preparation method of highly digestion-resistant recrystallized nano-starch, characterized in that, It includes the following steps: (1) Biological enzyme treatment: Treat the starch suspension with biological enzymes to obtain an enzymolysis solution, and inactivate the enzymes in the enzymolysis solution; (2) Alcohol precipitation treatment: Perform alcohol precipitation treatment on the enzyme-inactivated enzymolysis solution at the super gelatinization temperature, centrifuge to obtain a precipitate for retrogradation and freeze-drying treatment to obtain nano starch crystals; (3) High-temperature and high-humidity treatment: Recompound the nano starch crystals with pure water, perform heat preservation treatment in a high-temperature environment, centrifuge, and freeze-dry the obtained precipitate to obtain the high-resistant-digestibility recrystallized nano starch.
2. The preparation method according to claim 1, characterized in that, The biological enzyme is one or two of debranching enzyme and pullulanase, with a concentration of 10 - 250 npun per gram of starch, and the treatment time is 1 - 5 h.
3. The preparation method according to claim 1, characterized in that, The source of the starch is any one of corn, potato, wheat, cassava, sweet potato, and rice, and the liquid of the starch suspension is a phosphate buffer solution with pH = 5 - 6.
4. The preparation method according to claim 1, characterized in that, The enzyme inactivation is carried out at 80 - 100 °C.
5. The preparation method according to claim 1, wherein The conditions for alcohol precipitation treatment: Pour absolute ethanol into the enzyme-inactivated enzymolysis solution at the super gelatinization temperature until the volume ratio of ethanol to the enzyme-inactivated enzymolysis solution is 1 - 3:2, keep stirring during the process, the stirring time is 10 - 90 min, and the super gelatinization temperature is 70 - 100 °C.
6. The preparation method according to claim 1, wherein The conditions for retrogradation: The retrogradation temperature is 0 - 5 °C, and the retrogradation time is 24 - 72 h.
7. The preparation method according to claim 1, characterized in that, The mass ratio of nano starch crystals to pure water is 2:3 - 2:
8.
8. The preparation method according to claim 1, characterized in that, The conditions for heat preservation treatment in the high-temperature environment are: the temperature setting range is 70 - 100 °C, and the heat preservation time is 5 - 30 min.
9. The preparation method according to claim 1, wherein, The centrifugation conditions: The relative centrifugal force is 1000 - 5000×g, and the centrifugation time is 10 min.
10. The preparation method according to claim 1, characterized in that, The freeze-drying conditions: The freezing temperature is less than -50 °C, and the drying time is 24 - 48 h.
Citation Information
Patent Citations
Method for preparing slowly digestible wheat starch through coordination of biological enzyme and low-temperature freeze-thawing
CN103114114A
New technology for raising crystallization degree of starch nanoparticles by heat-moisture treatment
CN103224566A
Preparation method of corn starch nanocrystals
CN111019983A
Preparation method of high-content resistant starch
CN117070581A
Digestion-resistant starch and method for improving digestion resistance of starch
CN117327203A